GUIDE IN ENGLISH AS A MATERIAL FOR PROFESSIONAL COMPETENCE ACQUISITION BY STUDENTS OF TOURISTS' SPECIALTIES (ON THE EXAMPLE OF THE GUIDE SERIES 'AWESOME UKRAINE') - Nataliia E. Polishko; Neliia M. Blynova (Alfred Nobel University Publisher, 2021)
The article is devoted to the issues of learning English by students of bachelor's specialty "Tourism" and «Hotel and restaurant business». Since foreign language proficiency is one of the main competencies for a student of this specialty, the question of the methodology of its study is extremely relevant. In this article the specifics of the 'Awesome Ukraine' English guide-book is being researched. In English-speaking guides the specifics of the target audience should be carefully taken into consideration, since not all tourists are fluent in English as a foreign language. Therefore, for students of 'Tourism" and "Hotel and restaurant business" specialties referring to an English-language guide-book would be of a valuable assistance in methodological and linguistic aspects. Students will not only assimilate information about a certain monument or location, but will also adopt the proper way to present facts, assimilate necessary language patterns, and learn to apply them in practice. The publication makes an editorial, linguistic and methodological analysis of the 'AWESOME UKRAINE' series. These seven publications tell foreigners about Ukraine, it's most attractive and interesting locations, present one of the most respected IT centers. All of that can be used during lectures and practical classes for various English-language disciplines as didactic material. Text content in all editions is laconic; the material is described in simple and accessible English. One article about a certain monument or location occupies one-page spread, which is convenient for perception. Each topic material is illustrated with a thematic photo. The series is competently created, has a thoroughly thought-out concept for the embodiment of the text and illustrative material. The article demonstrates that the capabilities of a modern guide-book are able to perform not only informative but also a communicative function of a mediator in intercultural communication. Thanks to this fact, it becomes possible to effectively use this potential in the formation of basic competences and skills to productively implement professional activities for future professionals in tourism and hospitality industry.